2009
DOI: 10.1254/jphs.08204fp
|View full text |Cite
|
Sign up to set email alerts
|

Acemannan Stimulates Gingival Fibroblast Proliferation; Expressions of Keratinocyte Growth Factor-1, Vascular Endothelial Growth Factor, and Type I Collagen; and Wound Healing

Abstract: Abstract. Aloe vera has long been used as a traditional medicine for inducing wound healing. Gingival fibroblasts (GFs) play an important role in oral wound healing. In this study, we investigated the effects of acemannan, a polysaccharide extracted from Aloe vera gel, on GF proliferation; keratinocyte growth factor-1 (KGF-1), vascular endothelial growth factor (VEGF), and type I collagen production; and oral wound healing in rats. [ 3 H]-Thymidine incorporation assay and ELISA were used. Punch biopsy wounds w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
130
0
19

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(157 citation statements)
references
References 28 publications
3
130
0
19
Order By: Relevance
“…Similarly, Jettanacheawchankit et al 24 found that acemannan plays a significant role in the oral wound healing process via the induction of fibroblast proliferation and stimulation of keratinocyte growth factor-1 (KGF-1), vascular endothelial growth factor (VEGF), and type I collagen expressions. In a clinical trial with 40 patients with oral minor aphthous lesions, Babaee et al 25 observed that Aloe vera 2% oral gel is not only effective in decreasing the recurrent aphthous stomatitis patients' pain score and wound size but also decreases the aphthous wound healing period.…”
Section: Discussionmentioning
confidence: 98%
“…Similarly, Jettanacheawchankit et al 24 found that acemannan plays a significant role in the oral wound healing process via the induction of fibroblast proliferation and stimulation of keratinocyte growth factor-1 (KGF-1), vascular endothelial growth factor (VEGF), and type I collagen expressions. In a clinical trial with 40 patients with oral minor aphthous lesions, Babaee et al 25 observed that Aloe vera 2% oral gel is not only effective in decreasing the recurrent aphthous stomatitis patients' pain score and wound size but also decreases the aphthous wound healing period.…”
Section: Discussionmentioning
confidence: 98%
“…Wound healing of animals receiving Carbopol containing 0.5% ACE (w/w) was significantly better than that of the other groups (p<0.05). These findings suggest that ACE plays a significant role in the oral wound healing process via the induction of fibroblast proliferation and stimulation of KGF-1, VEGF, and type I collagen expressions [56] .…”
Section: Wound Healing Of Aloe Veramentioning
confidence: 73%
“…8,9 In addition, AV stimulates PGE2, TGF-β-1 and bFGF production and induces angiogenesis, which play important roles in the maintenance of mucosal integrity and wound healing. 31 Moreover, AV enhances production of kGF-1 and VEGF by g ing ival fibroblasts 32 and maintaines the wound moisturized, promotes epithelial cell migration, and enhances collagen maturation. 33 AgNPs exerts its healing effect by decreasing bacterial and fungal count at wound site.…”
Section: Discussionmentioning
confidence: 99%